2021
DOI: 10.1155/2021/6678958
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Artificial Intelligence Applications in Chinese Medicine Therapy

Abstract: To evaluate the importance of AI technologies in modernizing traditional Chinese medicine (TCM) therapy, this article presents the systematic review of the relevant literature and explains the beneficial effects of AI technology on the TCM treatment outcomes from the experience of famous and veteran Chinese medicines, including acupuncture, Tui Na massage, and Qigong practitioners. This study also focuses on the urgent necessity to apply AI technologies to develop therapeutic models on the theme “treating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…This research also focuses on the urgency of developing treatment models using artificial intelligence technology, with the theme of "treating diseases before they occur". In addition, the study also discussed the main bottlenecks and future prospects of the development of intelligent TCM treatment strategies [7]. Jia Yawei and other researchers found that the laser speckle blood flow imaging system can greatly evaluate the changes of skin blood flow during physiotherapy.…”
Section: Plantar Acupoint Physiotherapy Technology and Application Fi...mentioning
confidence: 99%
“…This research also focuses on the urgency of developing treatment models using artificial intelligence technology, with the theme of "treating diseases before they occur". In addition, the study also discussed the main bottlenecks and future prospects of the development of intelligent TCM treatment strategies [7]. Jia Yawei and other researchers found that the laser speckle blood flow imaging system can greatly evaluate the changes of skin blood flow during physiotherapy.…”
Section: Plantar Acupoint Physiotherapy Technology and Application Fi...mentioning
confidence: 99%
“…Babic et al, who apply artificial intelligence technology to medical-assisted treatment, suggested that regulators should better understand the relationship between consumers and medical artificial intelligence, especially the interaction method with diagnostic applications [5]. To assess the importance of artificial intelligence technology in the modernization of TCM treatment, Feng et al systematically reviewed the relevant literature in his article and explained the beneficial impact of artificial intelligence technology on TCM treatment outcomes [6]. Lan et al discussed the application of virtual reality technology in clinical medicine, especially in surgical training, pain management, and psychiatric treatment.…”
Section: Related Workmentioning
confidence: 99%
“…According to the National Health Interview Survey (NHIS) conducted in the United States, 33.2% of adults and 11.6% of children respond they use CAM, and 30% of the medical payments ($14.7 billion) were paid to CAM (Barnes et al, 2004;Barnes et al, 2008). AI is currently used for pattern diagnostics, symptoms classifications, and finding drug candidate substances in the CAM or traditional medicine fields (Zhang et al, 2020;Feng et al, 2021a;Alice et al, 2021).…”
Section: Introductionmentioning
confidence: 99%